EXPLORING THE LANDSCAPE OF PROJECT-BASED LEARNING IN WRITING SKILL: A SCOPING REVIEW PERSPECTIVE - Nur Nabila Azman; Nurul Ajleaa Abdul Rahman; Goh Ying Soon; Azman Che Mat; Nurul Farihah Rosli (Journal of Islamic, Social, Economics and Development, 2024)
Project-based learning is an instructional approach that practices learning around projects. This approach is not new, and many past studies have shown its effectiveness in language learning. This study examines the benefits and obstacles associated with project-based learning (PjBL) in the context of tertiary education, specifically in relation to the enhancement of English writing abilities. The primary focus of this investigation is on the viewpoints of teachers. The publications are obtained from reputable databases including Scopus, Google Scholar, ERIC, and Semantic Scholar. This study offers a comprehensive analysis of the existing literature, presenting useful insights into the benefits and constraints associated with the adoption of project-based learning (PjBL) among tertiary education instructors. The primary objective of this study is to make a scholarly contribution to the current body of literature by providing suggestions and practical applications for educators and researchers who are interested in employing project-based learning (PjBL) as a means to improve writing teaching in higher education. The significance of this study is centered around the necessity to develop efficient instructional approaches that can enhance the English writing abilities of students. This is considered a critical component of language competency. To summarize, this study aims to synthesize the current body of research about the advantages and challenges of project-based learning (PjBL) on the development of English writing abilities. These findings can be utilized by educators and researchers to inform their instructional techniques and to conduct further investigation in this field.